(3EgOGA GddWGFa ef CNHGQ GdWGFas - (3MSf Hf Ydj Hf jMji, CHh GdHbGA GdYLjej,J (B1113 (3g` s ((3bGSe Ydi GdMjOQ CHGOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ef Ydi ScGf MQa GdeMJQe HCUfGa GdESYGa hYhGWa GdCdWGaajbhd GdYHO Hf Gdebfi jMji Hf eaJi ecg hbGVjgG GdfSjN s
(3BNQgG (B:s
(3HYV GdCNhGf eeG CJb HYedg hYbdg (B,(3gi Yjf GdhgW hGNHQfi Gfg SeY Pdc ef QLGd KbGJ Gddg GYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B205 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B264s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs